2010
DOI: 10.1016/j.jconrel.2010.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of tissue drug concentrations with in vivo magnetic resonance images of polymer drug depot around arteriovenous graft

Abstract: Sustained delivery of anti-proliferative drugs to the perivascular area using an injectable polymeric platform is a strategy to inhibit vascular hyperplasia and stenosis. In this study, the concentrations of sirolimus in vascular tissues were evaluated after delivery using an injectable platform made of poly(lactic-co-glycolic acid)-polyethylene glycol-poly(lactic-co-glycolic acid) (PLGA-PEG-PLGA). In order to optimize the drug release profile, the effect of two solvents or solid loading of the sirolimus into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…The proliferation and migration of vascular smooth muscle cells and myofibroblasts into the neointimal layer can result in a pathologic narrowing of the access. 2 There have been many efforts to prevent stenosis through inhibiting smooth muscle cell proliferation and migration using local delivery of potent antiproliferative agents such as paclitaxel or sirolimus. [3][4][5][6][7][8][9] We previously reported that paclitaxel coating of ePTFE grafts was effective in suppressing such neointimal hyperplasia and stenosis.…”
mentioning
confidence: 99%
“…The proliferation and migration of vascular smooth muscle cells and myofibroblasts into the neointimal layer can result in a pathologic narrowing of the access. 2 There have been many efforts to prevent stenosis through inhibiting smooth muscle cell proliferation and migration using local delivery of potent antiproliferative agents such as paclitaxel or sirolimus. [3][4][5][6][7][8][9] We previously reported that paclitaxel coating of ePTFE grafts was effective in suppressing such neointimal hyperplasia and stenosis.…”
mentioning
confidence: 99%
“…The minced fat was placed perivascular to the vein and the wound was sutured closed and the animals were allowed to recover. For efficacy studies, a porcine model of arteriovenous graft that has been described in detail previously [14, 15, 35, 36] was used. In sedated animals, under sterile conditions, a spiral-reinforced expanded synthetic polytetrafluoroethylene (PTFE) graft (7-cm length, 6-mm internal diameter) was placed between the common carotid artery and the ipsilateral external jugular vein such that blood flow from the carotid was partially shunted into the vein via the interposing graft.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported the successful use of perivascular administration of sirolimus, an anti -proliferative immunosuppressant, using a biodegradable synthetic polymer to inhibit arteriovenous graft stenosis [14, 15]. However, swelling and exudate occurred at the site of polymer-drug administration in almost 17% of animals, suggesting the polymer-drug mixture may have triggered inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…A single application of a polymer gel incorporated with the antiproliferative agent, paclitaxel, did inhibit neointimal hyperplasia in AVG in a dog model (17). Repeat application of a sirolimus-laden polymer gel through ultrasoundguided injection to the vein-graft anastomosis significantly inhibited neointimal hyperplasia at 6 weeks in the swine AVG model (63,69). Perivascular application of expression vectors to alter in vivo vascular gene expression to promote better access outcomes has been reported.…”
Section: Perivascular Approachesmentioning
confidence: 96%